2020
DOI: 10.1186/s12906-020-03006-2
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits the growth of natural killer/T-cell lymphoma cells by modulating CaMKIIγ-c-Myc signaling pathway

Abstract: Background C-Myc overexpression is associated with poor prognosis and aggressive progression of natural killer/T-cell lymphoma (NKTCL). Matrine, a main alkaloid of the traditional Chinese herb Sophora flavescens Ait, has been shown to inhibit cellular proliferation and induce apoptosis of various cancer cells. The present study investigated the effects and possible mechanisms of matrine inhibiting the growth of natural killer/T-cell lymphoma cells. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Ma et al showed that matrine suppressed the growth of human chronic myeloid leukemia K562 cells with an IC 50 of 2 mM for 48 h treatment [13]. Our previous study showed that matrine inhibited human NKTCL NK92 cells for 48 h with IC 50 of 1.96 mM [16]. In current study, matrine inhibited the growth of DLBCL cell lines SU-DHL-16 and OCI-LY3 cells in a dose and time dependent manner.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Ma et al showed that matrine suppressed the growth of human chronic myeloid leukemia K562 cells with an IC 50 of 2 mM for 48 h treatment [13]. Our previous study showed that matrine inhibited human NKTCL NK92 cells for 48 h with IC 50 of 1.96 mM [16]. In current study, matrine inhibited the growth of DLBCL cell lines SU-DHL-16 and OCI-LY3 cells in a dose and time dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…The cells were collected. Total RNA extraction, cDNA synthesis and qPCR were performed as described previously [16]. Brie y, total RNA was isolated by TRIzol.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
See 3 more Smart Citations